Pengaruh Strategi Critical Incident Pada Hasil Pembelajaran IPA The Effect Of Critical Incident Strategy On Science Learning Output - Tiara Tiara; Ramadani; Ega Nia Maidita (Symbiotic: Journal of Biological Education and Science, 2020)
Critical incident is one of the learning strategies that can be used to improve the student ability in understanding of science. This study was conducted to determine the effect of critical incident strategy on students’ science learning output. The study used experimental design method by using pretest-posttest control group design. Population of this study was the second year students of SMPN 12 Kerinci. The subject was divided into two groups, which are the control and experimental class. The result showed that the number of students in the experimental class can achieve excellent score; it was increased from 3 students (at the pretest) to7 students (at the posttest). Meanwhile, it was not occurred in the control class. It indicates that this strategy can improve students’ learning output of science. Thus, Critical incident strategy has significant effect on students’ learning output based on t-test at the significance level α = 5% obtained tcount=2,85 while ttable=2,02 (2,85 > 2,02).